Identificação e sazonalidade dos constituintes de Kalanchoe pinnata (Lans) Pers. – planta com ação uterolítica e ansiolítica - Pereira, Kassia Martins Fernandes [UNIFESP] (2016)
Introduction: The Kalanchoe pinnata (Crassulacean) plant has a huge growth potential. It is specially used within Anthroposophic Medicine, where it has indication for anxiety and sleep disorders and for preterm labor prevention. Brazil's public health ministry recommends for further research regarding plants, in order to extend the range of safe therapeutic options offered to public health users (SUS). Objectives: To trace the phytochemical profile, evaluate it's composition and seasonality within various extraction mediums and seasons. Methods: The K. pinnata leaves were harvested and subjected to extraction in cool water, hot water, water:ethanol, dried-methanol, concentrate juice (undiluted), during summer and during winter. The anthroposophic medication was also analysed. The samples were analysed via High Performance Liquid Chromatography and Mass Spectrometry. Results: The plant's constituents were identified as hydroxycinnamic acids and flavonoids. The main components appeared in the following concentration sequence: Quercetin 3-O-?-L-arabinopyranosyl-(1?2)-?-L-rhamnopyranoside, Coumarylglucaric acid and Quercitrin. The medication also displayed Quercetin 3-O-?-L-arabinopyranosyl-(1?2)-?-L-rhamnopyranoside. The samples contents fluctuated according to extraction method and harvest season. The most concentred samples were the water-ethanol ones; whereas the summer samples showed a thorough component concentration, the winter ones had a larger concentration of the main components. Bufadienolides were not found in any extract. Conclusion: The applied methodology was able to trace the plant's profile. Flavonoids were the most evident class; with larger concentration in higher temperatures, with plenty sunlight exposure. The flavonoids seem to be responsible for the effects observed in other studies and clinic practice; therefore, future research regarding this plant is recommended.